2012
DOI: 10.3399/bjgp12x625201
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experiences of self-monitoring blood pressure and self-titration of medication: the TASMINH2 trial qualitative study

Abstract: BackgroundSelf-management of hypertension, comprising self-monitoring of blood pressure with selftitration of medication, improves blood pressure control, but little is known regarding the views of patients undertaking it. AimTo explore patients' views of self-monitoring blood pressure and self-titration of antihypertensive medication. Design and settingQualitative study embedded within the randomised controlled trial TASMINH2 (Telemonitoirng and Self Management in the Control of Hypertension) trial of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(118 citation statements)
references
References 23 publications
6
110
2
Order By: Relevance
“…A feasibility study done in lowrisk pregnant women showed a preference for blood pressure selfmonitoring with a reduced schedule of antenatal visits, and no change in anxiety levels [22]. Literature on blood pressure self-monitoring outside pregnancy indicates patients are confident at self-monitoring and report high levels of satisfaction and feelings of involvement, control, and support for their health [23,24]. In the current study similar findings for self-testing of urine are reported; women whose readings were used by HCPs felt valued and involved in their own care and reported positive experiences.…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…A feasibility study done in lowrisk pregnant women showed a preference for blood pressure selfmonitoring with a reduced schedule of antenatal visits, and no change in anxiety levels [22]. Literature on blood pressure self-monitoring outside pregnancy indicates patients are confident at self-monitoring and report high levels of satisfaction and feelings of involvement, control, and support for their health [23,24]. In the current study similar findings for self-testing of urine are reported; women whose readings were used by HCPs felt valued and involved in their own care and reported positive experiences.…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…Existing studies of home blood pressure monitoring have been largely undertaken within clinical populations, considering how people understand blood pressure, their motivations for undertaking monitoring and their communications with clinicians (e.g. Jones et al 2012, Vasileiou et al 2013, Tyson and McElduff, 2003. Rather than focusing on how people understand and interpret blood pressure numbers or how they respond to these numbers, we are interested here in the material and mundane aspects of independently undertaken blood pressure monitoring.…”
Section: The Case Of Home Blood Pressure Monitoringmentioning
confidence: 99%
“…Poor guidelines, lack of self-monitoring protocols, and suboptimal interpretation by health professionals of home BP readings are just a few reasons suggested by recent literature to explain why patients are currently met with a relative lack of enthusiasm when presenting HCPs and/or GPs with home monitoring data. 8,15 A more effective approach to successful integration must be adopted through theoretically based patient education guiding clinicians and patients through collaborative and shared discussions of patients' priorities, treatment planning, specific goals, and follow-ups. Such active consultations within a 'shared decision-making approach' are increasingly being observed in hypertension consultations.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…9,10 This is further supported by an increasing body of qualitative evidence showing patients want to understand more about their hypertension [11][12][13][14] and establishes links between self-monitoring and telemonitoring with medication adherence. [15][16][17][18][19] Two UK-based randomised controlled trials with embedded qualitative studies support the utility of self-monitoring, though authors do note that participant selection may also have inclusion bias. 15,16 These studies suggest patients felt confident about selfmonitoring, trusting multiple home readings more than a single office-based reading, and that self-monitoring as part of the telemonitoring intervention helped patients feel more engaged in the clinical management of their condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation